To review the effectiveness of project management in construction process - Noor Hafizatul Ashikin, Rozali (2015)
Now days, our construction industry is facing a lot of problems that mainly associated with its ineffectiveness work process. This phenomenon has been manifested by frequent news and critics about how lack of our construction industry and the impact of that, it cause of project delay and inferior quality. Therefore, there is an urgent need for construction industry to improved and overcomes this problems. Many efforts that have been done to improved and overcome performance of the construction industry reputation such as using alternative procurement system, adoption of tools and management philosophy from other industry and using to new technological advancement such as the used of modular construction in Malaysia. In view, the problems that face by the industry, this study has been undertaken with the aim to determine the strategies to improve the effectiveness of project management in construction process. The methodologies adopted for this study are the distribution of questionnaire survey. The findings from this study confirmed that the construction industry particularly in Malaysia need to be improved with regards of its effectiveness. There are also a lot of problems associated due to construction process, such as poor communication, poor site management, and poor site coordinator, lack of close monitor and control, and lack of focus to customer / end users expectation. The studies also determine that the strategies currently promoted to achieve the improvement are by using Industrialized Building System (IBS). Many organizational also integrate the quality management system such as ISO9001 and Total Quality Management System (TQM) in their process. The used of management tools and philosophy from other industry is not much popular strategies